2012
DOI: 10.1007/s10237-012-0394-7
|View full text |Cite
|
Sign up to set email alerts
|

Failure modelling of trabecular bone using a non-linear combined damage and fracture voxel finite element approach

Abstract: Trabecular bone tissue failure can be considered as consisting of two stages: damage and fracture; however, most failure analyses of 3D high-resolution trabecular bone samples are confined to damage mechanisms only, that is, without fracture. This study aims to develop a computational model of trabecular bone consisting of an explicit representation of complete failure, incorporating damage criteria, fracture criteria, cohesive forces, asymmetry and large deformation capabilities. Following parameter studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 76 publications
3
27
0
Order By: Relevance
“…49 In a nonlinear mFEA incorporating damage, the strains at which damage forms in trabeculae were determined to be À 0.0116 (compression) and 0.0069 (tension) when the model was calibrated against compression tests of ovine trabecular bone. 50 The corresponding fracture strain estimates were double the damage strains, and so a failure strain between 0.02 and 0.007 appears reasonable. This range could not be achieved for the Renders et al 35 relationship when the failure volume was less than 10%.…”
Section: Discussionmentioning
confidence: 94%
“…49 In a nonlinear mFEA incorporating damage, the strains at which damage forms in trabeculae were determined to be À 0.0116 (compression) and 0.0069 (tension) when the model was calibrated against compression tests of ovine trabecular bone. 50 The corresponding fracture strain estimates were double the damage strains, and so a failure strain between 0.02 and 0.007 appears reasonable. This range could not be achieved for the Renders et al 35 relationship when the failure volume was less than 10%.…”
Section: Discussionmentioning
confidence: 94%
“…The non-linear behaviour of microstructural trabecular bone models have also been modelled by reducing the elastic modulus of the trabecular material to 5% when critical principal strain is computed at a material point (Bayraktar et al 2004a;2004b;Niebur et al 2000;Guillén et al 2011;Verhulp et al 2008;Harrison et al 2012). Niebur et al (2000) based such criteria on macroscopic testing of cortical bone by Reilly and Burstein (1975).…”
Section: Discussionmentioning
confidence: 99%
“…Niebur et al (2000) based such criteria on macroscopic testing of cortical bone by Reilly and Burstein (1975). Under uniaxial compression Harrison et al (2012) incorporated material damage using the principal strain based criterion and fracture through element removal and cohesive forces in the trabecular microarchitecture. Also based on the testing of cortical bone specimens, Verhulp et al (2008) implemented the principal strain based criterion in addition to a perfectly-plastic VM plasticity formulation for the uniaxial compression testing of trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies reported in the literature adopted linear elastic constitutive law (Hara et al, 2002;Verhulp et al, 2006;Kim et al, 2007;Bevill and Keaveny, 2009;Wolfram et al, 2010;Vilayphiou et al, 2011;Torcasio et al, 2012;Gross et al, 2013;Harrison et al, 2013;Bauer et al, 2014) to assess elastic modulus at tissue level, to retrieve overall mechanical behavior at apparent level or finally to study the strain distribution. A number of non-linear models are reported in the literature, adopting both different constitutive law and failure criteria to try to replicate the force-displacement curve as experimentally measured at apparent level (Niebur et al, 2000;Bayraktar and Keaveny, 2004;Verhulp et al, 2008b;Sanyal et al, 2012;Wolfram et al, 2012;Harrison et al, 2013;Bauer et al, 2014;Baumann et al, 2016). However, there is lack of a clear consensus of the literature over which non-linear approach is the most suitable and reliable in identifying the overall failure in terms of both ultimate strain and loading curve.…”
mentioning
confidence: 99%